Cardiac tamponade after thrombectomy - Shruthi Sivakumar; Asher Gorantla; Wayne-Andrew Palmer; Anandita Kishore; Michael Schiable; Ekenedilichukwu Nnadi; Ammar Abdulfattah; Suzette Graham-Hill (Exploration of Cardiology, 2024)
Pulmonary embolism (PE) is the third leading cause of cardiovascular mortality worldwide. Percutaneous mechanical thrombectomy is indicated in patients with contraindications to thrombolysis. Complications include atrial or ventricular perforation causing tamponade. We describe one case of pericardial tamponade in an elderly woman who underwent thrombectomy for acute PE. An 88-year-old woman presented with acute shortness of breath. She was tachycardic, oxygen saturation of 80% and blood pressure of 95/57 mmHg. Bedside ultrasound showed a dilated right ventricle. Electrocardiogram showed large S wave in lead I, Q wave and inverted T wave in lead III. Computed tomography (CT) angiogram of the chest revealed an extensive saddle PE. Tissue plasminogen activator was deferred given patient’s age. Full dose anticoagulation was started and she underwent a successful percutaneous thrombectomy with FlowTriever device. Two hours later, she developed severe back pain and hypotension to 88/63 mmHg. Hemoglobin dropped from 13.7 g/dL to 8.8 g/dL. CT chest angiogram showed dense pericardial effusion, likely hemopericardium, with mass effect on the heart. Bedside pericardiocentesis was attempted and converted to pericardial window given sustained hypotension. She went into cardiac arrest. Emergent thoracotomy revealed significant hemothorax. The pericardium was opened yielding a blue, globally ischemic, and non-contracting heart. Cardiac massage and intra-cardiac epinephrine attempted unsuccessfully. Percutaneous thrombectomy using the large bore design FlowTriever system has shown promising results in reducing clot burden and improving hemodynamics. Attention must be paid to life threatening complications such as cardiac tamponade which can be precipitated by using these devices.